Peran Guru Ppkn Dalam Meningkatkan Sikap Nasionalisme Siswa Di SMP Negeri 2 Sumalata Timur - Tiara Akase; Zulaecha Ngiu; Saleh Al Hamid (Journal on Education, 2024)
This research aims to discuss the role of PPKn teachers in increasing students' nationalistic attitudes at SMP Negeri 2 Sumalata Timur. This research uses a qualitative method with a descriptive approach where data is obtained through observation, interviews and documentation stages. This is done for the sake of the accuracy of the data obtained. The research results show that the role of teachers in increasing students' nationalism has gone well in accordance with their duties and functions both in learning and outside of learning. Meanwhile, the obstacles faced by teachers in increasing students' nationalism are due to students' lack of attention in learning, self-awareness, rapid globalization, family, environment and peer interactions which influence students' nationalistic attitudes so that it needs strengthening and coaching so that students can carry out their duties and responsibilities as citizens. good country.